Giant bilateral adrenal leiomyoma: a case report - Calderón-González, María A.; Mena, Ana K. (International Journal of Research in Medical Sciences, 2024)
Adrenal leiomyoma is extremely rare and is thought to arise from the smooth muscle wall of the central adrenal vein and its branches; Clinically they may present as abdominal pain or flank pain. These tumors generally have a low biological potential. The surgical indication for adrenal tumors is based mainly on functionality and the risk of malignancy. 39-year-old male, with no significant history. Who comes to the general surgery outpatient clinic due to the presence of progressive abdominal distension and long-term abdominal pain. An abdominopelvic CT scan was performed, which revealed bilateral, well-circumscribed tumor with heterogeneous characteristics located in the left and right adrenal area, negative functional tests. An exploratory laparotomy was performed, revealing two giant adrenal tumors, definitive study reporting bilateral adrenal leiomyoma. We present a rare case of bilateral primary adrenal leiomyoma of which no similar case was found in the reviewed literature. These tumors are very difficult to diagnose preoperatively, as they are often not counted in adrenal samples and clinical suspicion is very low. As a result, they are diagnosed postoperatively after pathological examination of the surgical specimen. At the moment, early and complete surgical resection is the main treatment.